Docking and Pharmacokinetic Studies of Oxazolone Derivatives of p-Coumaric Acid as Anticancer Agents - Unavane, Supriya A. (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Cancer is a leading cause of mortality leading to millions of deaths worldwide annually. It is a group of diseases characterized by the uncontrolled growth and spread of abnormal cells in the body. Protein tyrosine kinases (PTKs) are enzymes that regulate key cellular processes such as cell growth, differentiation, and survival. Targeted therapies such as tyrosine kinase inhibitors have been developed to block the aberrant PTK activity. P-coumaric acid is a phenolic acid of hydroxycinnamic acid family abundantly available in various fruits, vegetables, and cereals. It exhibits a wide range of pharmacological activities. It is reported to be active against various types of cancers, and hence, derivatives of p-coumaric acid can be developed as potential anticancer agents. Methods: In this study, we have designed derivatives of p-coumaric acid in combination with oxazolone ring. These compounds were docked on vascular endothelial growth factor receptor (VEGFR) receptor using AutoDock vina. All the compounds were further evaluated for their physicochemical properties and drug likeliness. Results and Discussion: All the compounds showed good binding affinity for the receptor with binding energy ranging from −9.8 to −10.7 kcaL/moL. All compounds have good bioavailability and none showed any violation of Lipinski’s rule of five. Conclusion: The studies reveal that p-coumaric acid derivatives of oxazolones show good binding affinity for VEGFR. Monosubstitution on aromatic ring enhances the binding affinity whereas disubstitution causes a decrease in binding affinity. All the compounds possess good absorption, distribution, metabolism, and elimination properties, and hence, these molecules could be developed further as anticancer agents.